PD-L1 expression by tumor macrophages: regulation and signaling - Hartley, Genevieve, author; Dow, Steven, advisor; Schenkel, Alan, committee member; Gonzalez-Juarrero, Mercedes, committee member; Biller, Barbara, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Keywords: canine; macrophage; cancer; tumor; immune checkpoint